Prerequisites for a successful project management information system - Smith, Kenneth F. (Philippine Journal of Public Administration, 1990)
The use of the Management Information System (MIS) is seen as one way of improving the management of project implementation in Third World countries. This article outlines a recent study of MIS applications in a number of development projects, and summarizes users' and observers' perceptions about the utility of such MIS for project management One relatively successful USAID-assisted MIS project in the Philippines was scrutinized in-depth, while still other MIS applications were surveyed Twelve variables were also isolated and tested in an attempt to establish some common criteria for successful MIS `design and application. The study confirms that while there are really no guarantees for success in using MIS, the prospect for improved monitoring, management and evaluation of development activities can be increased substantially.